Perintah Menjaga Lisan dalam Perspektif Hadis - Gery Hummamul Hafid; Muflihah Muflihah (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about keeping the oral. This research uses an approach approach by applying descriptive analytical method. The object of this formal research is the science of hadith, while the material object is the hadith about keeping oral in the history of Malik No. 1563. The results and discussion of this study indicate that the status of quality hadith is shahih that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Malik No. 1563 provides learning for humans to always keep their mouths when speaking.